Akar Kerusuhan Etnis di Indonesia : Suatu Kajian Awal Konflik dan Disintegrasi Nasional di Era Reformasi - Usman Pelly (Antropologi Indonesia, 1999)
This article explores the roots of riots that have occurred in several cities and places in Indonesia, the author assumes that the accumulative and chronic social - economic gap shrouded by the ethnic and religious factors, underlined the occurrence of riots in the early Indonesian reformation era (May 1995). The differences in gaining access to economic resources, as well as the discriminative policies of the New Order Regime, created a social-economic gap between the ethnic groups in Indonesia. While some groups had privileges and easy access to economic resources, other did not. As a consequence, some groups were subject to oppression and marginalized. The potential for conflict increased structurally as marginal groups used ethnicity and religious attributes in framing the social-economic gap between them and the advantage groups. From the functionalist viewpoints, ethnicity can be seen as an easy way to heighten solidarity among people. The riots could be legitimated by using cared religious symbols. The author argues that the conflict among ethnic groups increased as a 'cultural protest' to the government's discriminative policy. The conflict does not represent the people's desire to return to their 'tribal' culture.